ANALISA KERAGAMAN DAN DOMINANSI GULMA DI LAHAN MINERAL DAN LAHAN GAMBUT PADA PERKEBUNAN KELAPA SAWIT RAKYAT - Hangger Gahara Mawandha; Titin Setyorini; Lukmantoro (Program Studi Agroteknologi INSTIPER, 2019)
The research aims to determine the diversity and the dominance of the weeds in mineral land and peat then compare the weeds diversity between both. The research was conducted in Pelalawan District, Riau, from April to May 2018. The research was conducted by a descriptive method. The sample was taken using a square plot measuring 0,9 x 0,9 meter with 10 until 15 replications. The plot sample was taken on a path in mineral land and peatland. The result shows that the diversity of the weeds was higher in mineral land (12 species) than in peatland (6 species). None of the species in mineral land and peatland are dominant species. Broadleaf weeds and fern species are a dominant weed type of both lands. Perennial weeds species is a dominant weed type of both lands. The weeds community of mineral land and peatland shows the different compositions based on the similarity index (IS Sorensen) caused by the different environment condition. Keyword: weeds, diversity, dominance, mineral land, peat land, smallholder oil palm